Asuhan Keperawatan Keluarga Dengan Tahap Perkembangan Usia Pertengahan Keluarga Bapak R Khususnya Pada Ibu M Dengan Masalah Gout Arthritis Terhadap Terapi Kompres Jahe Di Kampung Bayur Pintu 1000 Tangerang - Nur Ayu Fazri; Rina Puspita Sari; Muhammad Hasan Basri; Alfika Safitri (STIKes Ibnu Sina Ajibarang, 2023)
Middle age family or middle age begins when the last child leaves home and ends with retirement or death of one of the spouses. This stage usually begins when parents are around 45-59 years old. Gout or often called gout is a metabolic disease in which the body cannot control uric acid resulting in an accumulation of uric acid which causes pain in the bones and joints. One of the non-pharmacological pain management is ginger compresses because ginger itself contains active substance compounds from oleoresin which consists of gingerol and shoagaol, and zingeberence is a homologue of phenol through a heating process. Case study method by providing nursing care to Ms. M by compressing ginger to reduce joint pain due to gout.. The results of Mrs. M's case study showed that after implementing it for 5 days on Mrs. M, the results of pain decreased to a scale of 1. It can be concluded that the effectiveness of compresses with ginger can reduce joint pain due to gout.